Differences in susceptibility to ash dieback in Czech provenances of Fraxinus excelsior. Issue 4 (6th March 2016) - Havrdová, L.; Novotná, K.; Zahradník, D.; Buriánek, V.; Pešková, V.; Šrůtka, P.; Černý, K.
Summary: The impact of ash dieback caused by Hymenoscyphus fraxineus on 17 provenances of Fraxinus excelsior and one provenance of Fraxinus angustifolia was studied in an extensive field trial established in the Czech Republic prior to the H. fraxineus invasion in 1999. A difference in the level of resistance to ash dieback between the species was found: F. angustifolia was significantly less affected by the disease than F. excelsior . Moreover, particular provenances of F. excelsior showed important differences in the level of resistance to H. fraxineus . A relationship between the impact of ash dieback and altitude was also discovered – the provenances from altitudes above 600 m a.s.l. were less affected by the pathogen than were the provenances from lower areas. No difference in the impact of the disease among provenances of F. excelsior from different ecotopes (ravine, calcareous ravine and alluvial) was found. Substantial among‐tree variability in resistance to H. fraxineus was observed throughout the trial – promising genotypes (with crown defoliation up to 5%) were identified in all 18 tested provenances. In regard to this finding, it appears that the main source of resistance to the pathogen is probably at the individual genotype level in the trial. A secondary but massive attack by Hylesinus fraxini was identified in the trees that had been greatly damaged by ash dieback, and the beetle caused their health to deteriorate significantly. A significant negative effect of the presence of collar necroses caused by H. fraxineus and browse damage was also identified.